MATHEMATICAL MODELING OF THERMAL DESTRUCTION OF PEOPLE IN CASE OF ACCIDENTS - Mashyhina, P. B. (Science and Transport Progress, 2008)
The method to calculate the thermopollution when the fire ball was burning was developed. The method is based on numerical integration of 3D equation of energy. Velocity field is calculated using 3D model of potential flow. The results of numerical experiment are presented.